Sex differences in kinematics and temporal parameters of the grab start - Kollias, I.; Baltzopoulos, V.; Chatzinikolaou, K.; Tsirakos, D.; Vasiliadis, I. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The purpose of this study was to examine sex differences in the kinematic and temporal parameters of the grab start using twodimensional analysis. The main findings of the study are that male swimmers develop a higher take-off speed without significant delay on the block and the angle of projection is usually above the horizontal. This results in a longer flight period but improved horizontal displacement compared to the start of female swimmers.